On the banks of Plum Creek [compact disc, unabridged] - Wilder, Laura Ingalls, 1867-1957 ([Publisher not identified], 2003)
Based upon her childhood growing up in the Midwestern frontier, American novelist Laura Ingalls Wilder presents the Little House series, a literary collection of children's classics. Told in the third-person, the books follow central character Laura as she and her family experience pioneer life in the mid-late nineteenth century. In the series' fourth book, Laura's family leaves Kansas for a new life in Minnesota. There, the family falls on tough times when a plague of locusts razes their crops.